A paradigm for developing tqm-role stressors model and index - Teh, P.L.; Yong, C.C.; Arumugam, V. (2009)
TQM practices have been increasingly implemented in both manufacturing and service organizations, yet research has neglected the study of role stressors induce from the implementation of TQM practices. Drawing from the extant TQM and role stressors literature, this paper examines the relationship between TQM and role stressors by addressing three critical gaps: (1) conceptualizing the multidimensionality of TQM practices as a preventive approach to role stressors; (2) formulating TQM-Role Stressors index for the use of industrial benchmarking; and (3) constructing a model for assessing the nonlinear influences of TQM on role stressors. This study concludes with a discussion of potential practical applications of the TQM-Role Stressors index and model for longitudinal study aimed at deepening our understanding of the role of TQM practices in reducing undesirable role stressors experienced by employees.